Assessment of Serum Biochemical Changes in Hepatic Encephalopathy - Rauf, Amna; Rauf, Sidra (Pakistan Armed Forces Medical Journal, 2022)
Objective: To analyze the association of various biochemical changes with different grades of hepatic encephalopathy among patients of hepatitis C-related decompensated liver disease presenting at Pak Emirates Military Hospital. Rawalpindi, Pakistan. Study Design: Comparative cross-sectional study. Place and Duration of Study: Medicine and Gastroenterology Department of Pak Emirates Military Hospital (PEMH), Rawalpindi Pakistan, from Mar 2020 to Feb 2021. Methodology: This study was conducted on 100 patients with hepatitis C-related decompensated liver. A consultant medical specialist or gastroenterologist graded hepatic encephalopathy according to the West Haven criteria. Serum urea, creatinine, albumin and international normalized ratio were performed in all the patients at the time of grading of encephalopathy and derangement in the level of these parameters was analyzed with Grades of encephalopathy. Results: Out of 100 patients, in the final analysis, 66 were males, and 44 were females. The commonest aetiology of hepatic encephalopathy was Infection (33%) followed by Constipation (29%). 15 patients had Grade-1 encephalopathy, 43 had Grade-2, 26 had Grade-3 while 16 had Grade-4 encephalopathy. Deranged serum creatinine, international normalized ratio and albumin levels were significantly associated with a higher grade of hepatic encephalopathy (p-value<0.05) in our study participants. Conclusion: Biochemical markers studied in patients with hepatic encephalopathy secondary to hepatitis C-related decompensated chronic liver disease were deranged. In addition, creatinine, albumin and International normalized ratio were found to be more deranged in higher grades of encephalopathy.